Integrating Quranic Values Into Financial Management Strategies in Islamic Educational Institutions - Revi Rusdatul Jannah; Eka Maftuhatil Riskiyah; Ach. Hanuji Akbar (Journal of Educational Sciences, 2026)
Financial management is a key element in supporting the success of Islamic educational institutions, which must reflect Islamic values such as trustworthiness, transparency and justice. This study aims to analyze the integration of Quranic values in the financial management strategies of Islamic educational institutions. Using a descriptive qualitative approach based on literature study, this research identifies relevant Quranic principles, such as trustworthiness (QS. Al-Baqarah: 282), transparency (QS. At-Taubah: 105), and careful planning (QS. Al-Hasyr: 18). The results show that effective and efficient financial management of Islamic educational institutions requires the implementation of structured stages, namely planning (budgeting), implementation (accounting), and evaluation (auditing). Each of these stages must be carried out in accordance with Islamic values that emphasize trustworthiness, justice, and responsibility. In addition to these stages, the principles of transparency, accountability, effectiveness and efficiency are the main basis for financial management. By integrating systematic stages and principles based on Islamic values, Islamic education institutions can create professional, responsible and sustainable financial management to support quality and moral education.